How Do Judges Decide School Finance Cases? - Ethan Hutt; Daniel Klasik; Aaron Tang (Washington University Law Review, 2020)
There is an old riddle that asks, what do constitutional school funding lawsuits and birds have in common? The answer: every state has its own. Yet while almost every state has experienced hotly-contested school funding litigation, the results of these suits have been nearly impossible to predict. Scholars and advocates have struggled for decades to explain why some state courts rule for plaintiff school children—often resulting in billions of dollars in additional school spending—while others do not. If there is rough agreement on anything, it is that “the law” is not the answer: variation in the strength of state constitutional education clauses is uncorrelated with the odds of plaintiff success. Just what factors do explain different outcomes, though, is anybody’s guess. One researcher captured the academy’s state of frustration aptly when she suggested that whether a state’s school funding system will be invalidated “depends almost solely on the whimsy of the state supreme court justices themselves.” In this Article, we analyze an original data set of 313 state-level school funding decisions using multiple regression models. Our findings confirm that the relative strength of a state’s constitutional text regarding education has no bearing on school funding lawsuit outcomes. But we also reject the judicial whimsy hypothesis. Several variables— including the health of the national economy (as measured by GDP growth), Republican control over the state legislature, and an appointment-based mechanism of judicial selection—are significantly and positively correlated with the odds of a school funding system being declared unconstitutional. After presenting these findings, the Article discusses the important implications for school finance advocates and for constitutional and legal theory more broadly.
Keywords: School finance; Education law; State constitutional law; Constitutional law; Constitutional interpretation; Judicial decision making; School funding